THE PORTRAYAL OF WOMEN IN NGERI-NGERI SEDAP MOVIE: SOCIOLINGUISTICS STUDY - Simatupang, Ervina CM; Zuraida, Ida; Hendar, Hendar (English Review: Journal of English Education, 2024)
This study investigates the portrayal of women in the Indonesian film “Ngeri-Ngeri Sedap” movie through a sociolinguistics study. The research aims to explore how language and dialogue in the movie reflect and reinforce societal attitudes towards women, examining the representation of female characters and their interactions within the narrative. The collected data are analyzed by applying qualitative and descriptive method. The dialogues undergo thematic analysis to identify recurring themes related to gender roles, power dynamics, and language use. This approach allows for a comprehensive understanding of how women’s speech in the film reflects or diverges from established sociolinguistic patterns. Triangulation is employed by comparing the film's portrayal of women with existing literature on gender roles in Indonesian society and media, ensuring the validity of the findings (Baxter, 2019; Sunderland, 2020). The results indicate that the portrayal of women in Ngeri-Ngeri Sedap is shaped by cultural influences and prominent themes such as 5 Gender Roles as a woman, 5 Emotional Attachment, and 10 Gender Conflict and Tension. However in the film Ngeri-Ngeri Sedap by comparing woman image and man image it can be found that woman are often portrayed as inferior, weak, and marginalized, while men appear as superior, strong, and dominant. There are some symbolic resistances, but man’s power still cannot be fully seized by woman. As an obedient being, Sarma always does whatever her parents told her to do and feels she must obey completely. Never in her life does she disobey her parents. She then compared what her life to her brothers’. The result come to the fact that the brothers were able to do something freely and disobey their arents because they are men, not a woman like Sarma. The film portrays women as individuals expected to obey men’s commands. Women are also portrayed as being of lower status than men. The patriarchy in this movie is also very noticeable. This portrayal reflects and potentially reinforces societal views of patriarchy and gender hierarchy in Indonesian media